Chronic tick-borne encephalitis - E. G. Demianovskaia; V. V. Pogodina; N. G. Bochkova; E. I. Naumov; T. A. Snitur; L. S. Levina; M. S. Szherbinina; A. S. Vasiliev (Лечащий Врач)
The article is devoted to Kozhevnikov's epilepsy, one of the most common and, in fact, pathognomonic manifestations of the chronic course of tick-borne encephalitis. The stages in its development, the types of the course of the formed Kozhevnikovskaya epilepsy, and approaches to therapy are described. This material presents a unique case of chronic tick-borne encephalitis (TBE) (47 years from the beginning of the disease and more than 30 years after vaccination). It is shown that the delayed development of severe neurological symptoms and disease progression occur against the background of dysimmunoglobulinemia. The strain isolated from the patient had high neurovirulence for white mice, was highly neuroinvasive, and belong to the Siberian subtype of tick-borne encephalitis virus (TBEV). As TBE progressed, a polystrain immune response and a stressed immune response with high antibody avidity developed (30-32 years after vaccination). In the neurological status – pecular postencephalitic changes with elements of cortical motor epilepsy. No significant cognitive defect was detected.